Hubungan antara kualiti pengajaran dan pembelajaran dengan kepuasan pelajar: satu tinjauan - Tang, Swee Mei; Lim, Kong Teong (Sekolah Pengurusan, Universiti Utara Malaysia, 2002)
This study investigates the impact of various teaching and learning factors on students satisfaction with their degree programme. It applies established theory from customer sutisfaction and educational psychology research to a sample of students. A total of 112 students undertaking undergraduate degree in Human Resource Management were involved in this study. Research results indicate that teaching and learning quality factors were strongly positive related to students satisfaction and explained 31.5 per cent of the variance in students degree programme satisfaction.